Epinephelus labriformis - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Epinephelus labriformis (Jenyns, 1840). Flag Cabrilla or Starry Grouper. To 60 cm (23.6 in) TL (Robertson and Allen 2008). Mission Bay, southern California (Craig et al. 2006) to upper Gulf of California (Heemstra in Fischer et al. 1995) to Chile (Fricke et al. 2020), including Islas Galápagos (Grove and Lavenberg 1997). Depth: intertidal to at least 50 m (164 ft) (min.: Weaver 1970; max.: McCosker et al. 1997). Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 146, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008